IUEE
EU
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
Rehnuma123
Mar 2, 2018, 8:02:10 AM
30
Solve for y. 3(y-3)=6y
+3
(
1
) Answers
BreBre8424
Mar 2, 2018, 2:39:56 PM
3(y-3)=6y 3y+6=6y 6=3y 6/3=3y/3 2=y
Add answer
Sign in
Sign up
Related Questions
Solve for y. 3(y-3)=6y
solve for y 3x+6y=3 5x-y=27
Solve for y: 2x-6y=12
Solve for y. 7y - 6y - 10 = 13
Solve for y 4x-6 x+6y
solve for y 7y - 6y - 10 = 13
Solve the equation 3x + 6y = 18 for y
solve the equation for y 2x+6y=13
Solve the inequality for y. 7/2y - 3 < -6y + 7 Simplify your answer as much as possible.
Solve for y. 8x+6y=10. Please show steps